Response of Broilers with The Addition of Herbs (Miana Leaf Flour and African Leaf Flour) in the Broiler Ration - Nelzi Fati; Toni Malvin; Debby Syukriani; Irzal Irda; Dihan Kurnia (Jurnal Ternak : Jurnal Ilmiah Fakultas Peternakan Universitas Islam Lamongan, 2022)
The purpose of this study is to determine the response of broilers to the addition of African leaf flour and Miana leaves. This study used a completely randomized design. Day old broilers (DOC) 90 tails were randomly divided into 6 treatments and 3 replicates, with each replicate consisting of 5 tails. The six treatments were: A (excluding African Leaf Powder (TDA) and Miana Leaf Powder (TDM)), B (Added 4% TDA), C (Added 4% TDM), D (Added 2% TDA + 2% TDM), E (addition of 1% TDA + 3% TDM) and F (addition of 3% TDA + 1% TDM) were added to the self-stirring ration. The measured parameters were PBB, ration consumption, ration conversion, and carcass percentage. The results obtained from the addition of African leaf meal and Miana leaf meal had no significant effect (P> 0.05) on body weight, ration consumption, ration conversion and carcass percentage. The addition of African leaf meal and Miana leaf can be tolerated up to 4% in the broiler ration.